A Bibliometric Analysis of Advanced Healthcare Materials: Research Trends of Biomaterials in Healthcare Application. Issue 10 (17th February 2021) - Zhu, Shuang; Liu, Yaping; Gu, Zhanjun; Zhao, Yuliang
Abstract: In the field of biomaterials for healthcare applications, Advanced Healthcare Materials (AHM) has become one of the leading journals. Since 2011, AHM keeps bringing the latest research results in biomaterial science aimed at promoting human health. Nowadays, bibliometrics, of which methodological approaches can quantitively and qualitatively analyze the research performance of journals or subject fields, has attracted considerable attention among the scientific community. A general bibliometric overview of the research performance of AHM is presented. With the aid of Web of Science Core Collection database and VOSviewer software, the annual publication, the most prolific and influential authors/countries from AHM is identified. In addition, the most cited documents and keyword cooccurrence network analysis allow to recognize the major research topics in AHM. At last, the summary of current research trends based on AHM bibliometric analysis, several considerations for the clinical translation of biomaterials, and prospects to advance the field are also proposed. This editorial presents major research trends in the field of engineered materials for healthcare applications. Abstract : This article provides a bibliometric analysis of Advanced Healthcare Materials to recognize the most prolific and influential authors/countries, and major research topics in the field of biomaterials for healthcare applications. In addition, considerations for the clinical translation of biomaterials, and prospects to advance the field are also proposed.